Characterization of dual nano-size effects of ACC-cellulose nanofibrils on crystallization behavior of hydrophilic poly(vinyl alcohol) - Gento Ishikawa; Tetsuo Kondo (Journal of Wood Science, 2021)
Abstract This study attempts to clarify thermodynamic quantification on interaction between poly(vinyl alcohol) (PVA) and wood-derived cellulose nanofibrils (CNFs) obtained by aqueous counter collision (ACC) method. Aqueous mixtures of PVA/ACC-CNFs with various fiber widths were cast as the target materials. The interfacial interactions between the two components were characterized through thermodynamic evaluation of the crystalline PVA component as a probe in the cast mixture. As the result, surface properties of the ACC-CNFs found to reflect on the crystallization behavior of the interacted PVA component, resulting in dual nano-size effects of either diluent or nucleating agent. Melting point depression behaviors of the PVA component indicated that ACC-CNFs with thinner widths induced nucleation effects on PVA crystallization, whereas ACC-CNFs with ca. 100 nm in width encouraged diluent effects on PVA components. It is noted that this trend found to be reverse to the case for PVA/ACC-CNFs of bacterial nanocellulose previously reported.